PENYIMPANGAN MAKNA DENGAN HOMONIMI DALAM WACANA MEME (KAJIAN SEMANTIK) - Sukardi, Mochamad Ighfir; Sumarlam, Sumarlam; Marmanto, Sri (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2018)
The objectives of this study are: (1) to describe how the use of homonyms creates semantic deviation as a strategy to build humor in memes, and (2) to describe the patterns of semantic deviation that utilize homonyms. This research is a descriptive qualitative study. Data were collected using the observation method with advanced note-taking techniques. Data analysis employed the referential equivalent method with comparative techniques to support coding, reduction, presentation, and interpretation in line with the qualitative research framework. The findings of this study indicate that the use of homonymic meaning relations includes basic words, derivations, foreign terms, and slang. Semantic deviations utilizing homonyms were found to occur due to euphemisms, naming, and pauses. In addition to homonyms, the use of homophones and homographs through word abbreviations was also observed. Three patterns were identified in creating semantic deviations using homonyms: (1) the deviated word is accompanied by explanatory text, (2) the deviated word is paired with an image as an explanation, and (3) the deviated word does not appear as a linguistic symbol but is implied through an image with text as clarification. The key elements driving semantic deviation in memes are images and the use of collocations. Proper collocations effectively mislead the reader before surprising them with the secondary meaning. This research provides a valuable framework for analyzing humor in digital media and broadens the scope of linguistic studies by emphasizing the relationship between meaning, creativity, and audience interpretation.